2012
DOI: 10.3892/ijo.2012.1644
|View full text |Cite
|
Sign up to set email alerts
|

Differential DNA copy number aberrations in the progression of cervical lesions to invasive cervical carcinoma

Abstract: Host genomic alterations in addition to human papillomavirus (HPV) are needed for cervical precursor lesions to progress to invasive cancer because only a small percentage of women infected by the virus develop disease. However, the genomic alterations during the progression of cervical lesions have not been systematically examined. The aim of this study was to identify differential genomic alterations among cervical intraepithelial neoplasia CIN1, CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 40 publications
(48 reference statements)
3
12
1
1
Order By: Relevance
“…Our study showed that rs2285947 A allele was associated with an increased risk of ovarian cancer risk in Han Chinese women, consistent with the findings in lung cancer, non-cardia gastric cancer, and esophageal squamous-cell carcinoma by Jin et al (2012). Furthermore, it has been reported that several other loci at 7p15.3 were associated with many kinds of cancers, such as multiple myeloma (rs4487645) (Broderick et al, 2012;Martino et al, 2012) and lung cancer (rs2710994) (Xun et al, 2011), and DNA copy number aberrations (DCNAs) at 7p15.3 increased the risk of invasive cervical carcinoma (Oh et al, 2012). All these findings provided evidence that genetic variants at 7p15.3 are potentially important susceptibility loci associated with the development of multiple cancers.…”
Section: Discussionsupporting
confidence: 72%
“…Our study showed that rs2285947 A allele was associated with an increased risk of ovarian cancer risk in Han Chinese women, consistent with the findings in lung cancer, non-cardia gastric cancer, and esophageal squamous-cell carcinoma by Jin et al (2012). Furthermore, it has been reported that several other loci at 7p15.3 were associated with many kinds of cancers, such as multiple myeloma (rs4487645) (Broderick et al, 2012;Martino et al, 2012) and lung cancer (rs2710994) (Xun et al, 2011), and DNA copy number aberrations (DCNAs) at 7p15.3 increased the risk of invasive cervical carcinoma (Oh et al, 2012). All these findings provided evidence that genetic variants at 7p15.3 are potentially important susceptibility loci associated with the development of multiple cancers.…”
Section: Discussionsupporting
confidence: 72%
“…25 It has been reported that changes in copy number variations at 7p15.3 have also been found to be associated with a risk of invasive cervical carcinoma. 26 The LRFN2 protein is a member of the SALM family that shows interaction with the N-methyld-aspartate (NMDA) receptor. 16 Methylation of the 2B receptor of NMDA has been observed to serve as a susceptible gene for multiple cancers through the LRFN2-NMDA receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Otros estudios han demostrado perfiles de expresión diferencial entre tejido normal, lesiones precursoras (NIC) y tejidos con cáncer provenientes del cuello uterino 19,20,87,93,102,128 . Wilting et al realizaron un análisis sobre los patrones de expresión de miRNAs entre tejidos cervicales normales, lesiones precursoras (NIC II, III) y tejidos cancerosos del cuello uterino, mostraron 33 miRNAs con perfiles de expresiones diferencial concordante; 18 miRNAs sobre-expresados (Let7i, miR-19b, miR-21, miR-25, miR-28-5p, miR30e, miR-34a, miR-34b*, miR-92a, miR-92b, miR106b, miR-146a, miR-181d, miR-200a*, miR-206, miR-338-5p, miR-592 y miR-595) y 15 miRNAs infra-expresados (miR-23b, miR-134, miR-149, miR-193b, miR-203, miR-210, miR-296-5p, miR-365, miR-370, miR-493, miR-572, miR-575, miR-617, miR-622 y miR-638) 51 .…”
Section: Perfiles De Expresión De Los Mirnas En Diferentes Etapas Delunclassified